1970
DOI: 10.3329/taj.v21i1.3218
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Pathological Profile of Liver Abscess in a Teaching Hospital

Abstract: The study was conducted to assess the clinico-pathological profile of 50 liver abscess cases. This study showed that liver abscess is more common in male than in female. In present study Amoebic Liver Abscess (ALA) is much more common than Pyogenic Liver Abscess (PLA) and almost all the cases belonged to low or medium socio-economic class from rural areas. This may be due to poor living conditions, over crowding and unhygienic practices which leads to fecal contamination of food and drinks which help in transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
15
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 10 publications
7
15
1
Order By: Relevance
“…Pleural effusion was seen in 12% (n=6) cases whereas ascites was observed in 6% cases. Similar finding was reported by Siddiqui et al 8 Other complications like sepsis, multi-organ dysfunction and death were not seen in present study which could be attributed to the early diagnosis with prompt and aggressive treatment of the disease. Another reason being the smaller number of sample size of present study.…”
Section: 7supporting
confidence: 79%
See 1 more Smart Citation
“…Pleural effusion was seen in 12% (n=6) cases whereas ascites was observed in 6% cases. Similar finding was reported by Siddiqui et al 8 Other complications like sepsis, multi-organ dysfunction and death were not seen in present study which could be attributed to the early diagnosis with prompt and aggressive treatment of the disease. Another reason being the smaller number of sample size of present study.…”
Section: 7supporting
confidence: 79%
“…Hence the differentiation is essential for effective treatment. 8 In this article, we present the study of clinical, lab parameters and management of suspected Department of Medicine, Hamdard Institute of Medical Sciences and Research and Hakeem Abdul Hameed Centenary Hospital, New Delhi, India liver abscess patients, so that an early diagnosis can be made and prompt treatment can be started and complications can be prevented.…”
Section: Introductionmentioning
confidence: 99%
“…8 Siddiqui et al reported that according to USG report 70% patients were having single abscess and the rest 30% had multiple abscesses. 6 This pattern of involvement has also been reported in previous series on ALA by Sharma et al, Mukhopadhyay et al and Ghosh et al [10][11][12] In present study, chest X-ray abnormality was more in PLA (50%) compared to ALA group (35.8%). Reports of Choudhary et al reported that chest X-ray finding were abnormal in 39% of cases and was comparable to present study findings.…”
Section: Discussionsupporting
confidence: 75%
“…4 Most of the patients in present study with liver abscess were in middle age with patients in second to fourth decade accounting for55.2% of the cases which is comparable to other study done by Grorgia et al 5 Siddiqui et al reported that in case of ALA most common age group was 31-40 and in group of PLA 41-50 age group was more affected. 6 In our study there was high incidence of liver abscess in males (77.61%), as seen in a study by Huang et al (96%). A similar study done by Choudhary et al also reported similar age group (30-60 years) in liver abscess patients with male preponderance (72%).…”
Section: Discussionsupporting
confidence: 74%
“…A few investigators documented some sociodemographic aspects of these patients attended at RMCH, however, spectra of morbidity and mortality of ALA were not reported in those studies [9, 10]. More over, precise geographical distribution of ALA cases in the northern areas was not recorded by any investigator.…”
Section: Introductionmentioning
confidence: 99%